Risk and crisis management in the public sector - Drennan, Lynn T. 1953-; McConnell, Allan 1957-; Stark, Alastair (Routledge masters in public management series, 2015)
Risk and Crisis Management in the Public Sector Second Edition responds to these challenges by presenting the only guide for public mangers and public management students which combines lessons about risk and crisis management together in a single, accessible text. It equips readers with the knowledge and skills necessary to treat risks and it outlines the steps through which public managers can take to prepare, respond and recover from crisis episodes. This exciting new edition enhances the original text with contemporary cases and a greater focus on the international, trans-boundary and multi-agency dimensions of risk and crisis management. These enhancements reflect the fact that today's public manager must increasingly operate within a global and interdependent governance contex